2016
DOI: 10.1007/s00477-016-1247-1
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Spatial analysis and temporal trends of daily precipitation concentration in the Mantaro River basin: central Andes of Peru

Abstract: section it should say: In terms of average values, the analysis of daily rainfall indicates that low-intensity events account for 36 % of rainy days but only approximately 9 % of the total rain amount. In contrast, high-and very high-intensity events account for 37 % of rainy days and approximately 72 % of the total rain amount.In the conclusion section it should say: The analysis indicates that low-intensity events account for an average of 36 % of rainy days, contributing approximately 9 % of the total rain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Using polarimetric radars, operating in different bands (S, X, C, and W), rainfall rate estimation by reflectivity can be improved by different combinations of polarimetric parameters besides Z, so as differential reflectivity dry or wet seasons [18]. Using data of daily precipitation, [21] found that 35% of the rainiest days generate 71% of the amount of the total rain, approximately. Similarly, [11] using data of the Tropical Rainfall Measuring Mission precipitation radar (PR-TRMM) and Global Precipitation Measurement precipitation radar in Ku band (PRKu-GPM) found that percentages of occurrence of convective and stratiform precipitation in the areas of the Andes are 30% and 70% while their cumulative contributions to rainfall are 54% and 46%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Using polarimetric radars, operating in different bands (S, X, C, and W), rainfall rate estimation by reflectivity can be improved by different combinations of polarimetric parameters besides Z, so as differential reflectivity dry or wet seasons [18]. Using data of daily precipitation, [21] found that 35% of the rainiest days generate 71% of the amount of the total rain, approximately. Similarly, [11] using data of the Tropical Rainfall Measuring Mission precipitation radar (PR-TRMM) and Global Precipitation Measurement precipitation radar in Ku band (PRKu-GPM) found that percentages of occurrence of convective and stratiform precipitation in the areas of the Andes are 30% and 70% while their cumulative contributions to rainfall are 54% and 46%, respectively.…”
Section: Introductionmentioning
confidence: 99%